Rare Case: Ovarian Cysts in Child - Tubagus Odih R Wahid (Fakultas Kedokteran Universitas Riau, 2022)
An ovarian cyst is a sac filled with liquid or semiliquid material that arises in an ovary. Those cysts were mostly found in women aged 20-50 years. The incidence is 10: 100.000 women. This report reports a case of a child patient aged two years who came to Arifin Achmad Hospital with a chief complaint there is a mass in the lower abdomen area. From the physical examination, the lump in the lower abdomen area was obtained. We performed, laparotomy exploration with cystectomy and found a left ovarian cyst size 12 x 12 x 15 cm.